Nationella minoriteter och det kommunala ansvaret: En fallstudie om Uddevalla kommun och den sverigefinska minoriteten - Stenman, Sebastian (2018)
Minority languages has in a historical perspective been marginalised in Sweden. At the year of 2000 were 5 national minorities and their languages officially recognised as minority languages (Finnish, Meänkieli, Sami, Romani and Yiddish). Nine years later a Swedish law on minority rights was introduced (SFS 2009:724). The law put a large responsibility on municipalities to protect and promote the minority languages. The law also created an opportunity for municipalities to voluntarily become an administrative area for three of the minority languages (Finnish, Meänkieli and Sami). In the administrative areas are the minority rights strengthen. This study examines the case of Uddevalla municipality and the national minority Swedish Finns. This minority is struggling to retain their language and Uddevalla municipality has become an administrative area for the Finnish language. The purpose is to examine views of different types of work in the public administration who aims to strengthen and preserve the Finnish minority language. More specifically it focuses on implementation, accountability and the multicultural ideology which the minority rights framework is built upon. The data used in the study are both interviews with the Swedish minority representatives, public officials, politicians and official documents from Uddevalla municipality. Therefore, the method for the data collection in this study is qualitative interviews. The data were analysed by using a type of qualitative content analysis. The theories used are connected to implementation of political decisions but also to multiculturalism. Along with multiculturalism is also assimilation used as a theoretical concept. Findings shows that multicultural arguments weren’t used when Uddevalla became an administrative area for the Finnish language. Moreover, it identifies different types of important actors in the implementation of minority rights. The implementation is operated in a satisfying way, but there are organisational issues related to it. The ...